Effects of sauna bath on heart failure: A systematic review and meta‐analysis - Källström, Miikka (Clin Cardiol, 2018)
BACKGROUND: Sauna bath has potential as a lifestyle treatment modality for heart failure (HF). It is important to analyze the current evidence to help suggest paths of future study and potential for clinical application. HYPOTHESIS: Sauna bath has a positive effect on HF patients. METHODS: PubMed, Cochrane Library, and CINAHL databases were searched to identify randomized and nonrandomized controlled studies to compare effects of sauna bath with no sauna bath. Studies were searched for both infrared sauna bath and Finnish sauna bath. The strength of evidence was rated using a modified GRADE approach. Out of 1444 studies, nine met the inclusion criteria and were included in this review. Seven of these nine studies were included in the meta‐analysis. Only studies with infrared sauna bath met the inclusion criteria. RESULTS: In the meta‐analysis, exposure to an infrared sauna bath in 60°C for 15 minutes, followed by a 30‐minute rest in warm environment, five times a week for 2 to 4 weeks, was associated with a significant reduction in B‐type natriuretic peptide, cardiothoracic ratio, and an improvement in left‐ventricular ejection fraction. There was no significant effect on left‐ventricular end‐diastolic diameter, left atrial diameter, systolic blood pressure, or diastolic blood pressure. The strength of evidence varied from moderate to insufficient. CONCLUSION: Infrared sauna bath was associated with short‐term improvement in cardiac function. More evidence is needed about long‐term effects of sauna bath and the effects of a Finnish sauna on cardiovascular health among patients with HF or other cardiovascular diseases.